2008
DOI: 10.3390/ijms9050736
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Preliminary Crystallographic Analysis of a New Lys49-PLA2 from B. Jararacussu

Abstract: BjVIII is a new myotoxic Lys49-PLA2 isolated from Bothrops jararacussu venom that exhibits atypical effects on human platelet aggregation. To better understand the mode of action of BjVIII, crystallographic studies were initiated. Two crystal forms were obtained, both containing two molecules in the asymmetric unit (ASU). Synchrotron radiation diffraction data were collected to 2.0Å resolution and 1.9Å resolution for crystals belonging to the space group P 2 1 2 1 2 1 (a = 48.4Å, b = 65.3Å, c = 84.3Å) and spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…They are responsible for multiple pharmacological effects, some of which are dependent on catalytic activity and others of which are not. The pharmacological or biological effects that do not depend on enzymatic activity are driven by other pharmacological regions or sites that include calcium-binding loop, beta-wing and C-terminal region [16,19,23,24]. The precise location or mapping of these pharmacological sites is not easy to find due to the fact that the residues involved in myotoxicity and neurotoxicity significantly overlap, suggesting that multiple biological effects observed in many snake venom PLA 2 s are a consequence of superposed structural determinants on the protein surface [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are responsible for multiple pharmacological effects, some of which are dependent on catalytic activity and others of which are not. The pharmacological or biological effects that do not depend on enzymatic activity are driven by other pharmacological regions or sites that include calcium-binding loop, beta-wing and C-terminal region [16,19,23,24]. The precise location or mapping of these pharmacological sites is not easy to find due to the fact that the residues involved in myotoxicity and neurotoxicity significantly overlap, suggesting that multiple biological effects observed in many snake venom PLA 2 s are a consequence of superposed structural determinants on the protein surface [24].…”
Section: Discussionmentioning
confidence: 99%
“…The platelet aggregation activities were conducted as described by Oliveira et al [18] and dos Santos et al [19]. Venous blood was collected with informed consent from healthy volunteers who formally denied taking any medication in the previous 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…These effects are similar to those induced by the venom obtained from Crotalus species. It has been shown that convulxin, other class of C-type lectin from Crotalus durissus ssp., induced similar insulin secretion at both sub-(2.8 mM) and suprathreshold (16.7 mM) glucose concentrations (21).…”
Section: Discussionmentioning
confidence: 79%
“…For the first fractionation, whole venom was purified following the protocols described by dos Santos et al (21). In the second step, the whole venom (50 mg) was dissolved in 1 mL of calcium Trisbase saline (CTBS; Tris 20 mM, NaCl 150 mM, CaCl 2 5 mM, pH 7.5).…”
Section: Venommentioning
confidence: 99%
“…Purification of sPLA2 from whole venom was performed as previously described (16). 10 mg of the crude venom were dissolved in 250 μl of loading buffer (0.05 M Tris-HCl, pH 8.0) and centrifuged at 4,500 g for 5 min.…”
Section: Purification Of Spla2mentioning
confidence: 99%